2021
DOI: 10.1017/inp.2021.31
|View full text |Cite
|
Sign up to set email alerts
|

Indaziflam controls nonnative Alyssum spp. but negatively affects native forbs in sagebrush steppe

Abstract: Non-native plant invasions can have devastating effects on native plant communities; conversely management efforts can have non-target and deleterious impacts on desirable plants. In the arid sagebrush steppe rangelands of the western United States, non-native winter annual species affect forage production and biodiversity. One method proposed to control these species is to suppress the soil seed bank using the pre-emergent herbicide indaziflam. Our goal was to evaluate the efficacy of indaziflam to control no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 41 publications
(52 reference statements)
1
11
0
Order By: Relevance
“…If the seed bank were dominated by nonnative annual species that were homogenously distributed across a landscape, a treatment to deplete the entire seed bank and then reseed may make sense (Sebastian et al 2017a). However, these data suggest that a seed bank depletion treatment could deplete both the nonnative seed bank and potentially deplete a robust native seed bank at a site such as this (Meyer-Morey et al 2021).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…If the seed bank were dominated by nonnative annual species that were homogenously distributed across a landscape, a treatment to deplete the entire seed bank and then reseed may make sense (Sebastian et al 2017a). However, these data suggest that a seed bank depletion treatment could deplete both the nonnative seed bank and potentially deplete a robust native seed bank at a site such as this (Meyer-Morey et al 2021).…”
Section: Discussionmentioning
confidence: 91%
“…However, the spatial and vertical distributions of the native and nonnative soil seed bank present a challenge to management of the nonnative seed bank at this site (Knapp 1996, Humphrey and Schupp 2001, Gioria and Pyšek 2016, Rayburn et al 2016). Meyer-Morey et al (2021) found that pre-emergent herbicides such as Rejuvra ® have the potential to negatively impact and deplete the seed bank of native grasses and forbs, which were large components of the seed bank here (32.5% perennial grasses, 19.5% annual forbs, and 5% perennial forbs and subshrubs). Studies have found that pre-emergent herbicides do not have a significant impact on the standing perennial vegetation of a site (Clark et al 2019), but native perennials were found relatively infrequently across the Two Road Fire site (Table 1).…”
Section: Conclusion and Management Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an indication that it may harm some native forbs (Meyer-Morey et al 2021), and it could possibly inhibit seed germination and the establishment of commonly used grasses for restoration practices (Terry 2021). However, White Dome Nature Preserve is not an actively seeded conservancy and the focus of this study was understanding how indaziflam would affect the key plants commonly found in ideal poppy habitat.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research (with early trials) suggests that the chemical indaziflam can control cheatgrass for ≥ 3 yr with no negative effects on perennial species richness or abundance (Sebastian et al 2017b; Clark et al 2019). However, other researchers found indaziflam can have negative impacts on native forbs, especially annuals (Meyer-Morey et al 2021). Chemicals such as tebuthiuron have been used to thin or remove sagebrush or encroaching trees to induce a response in herbaceous vegetation, but from a fuels standpoint the treatment has little impact on predicted fire behavior since sagebrush wood is left on site with no reduction in fuel bed height (Ellsworth et al 2022).…”
Section: Fuel Treatment Methods Used In the Sagebrush Biomementioning
confidence: 99%